PARTICIPATORY MANAGEMENT IN IMPROVING THE QUALITY OF MADRASAH - Eviyana Eviyana; Nirva Diana; Idham Kholid; Rubhan Masykur (Edukasi Islami: Jurnal Pendidikan Islam, 2020)
Abstract:The essence of participatory management is covered in all concepts, namely: First, the existence of planning, organizing, directing, and monitoring activities; Second, there is more than one person or party involved; Third, there is a goal to be achieved; Fourth, there is the use of organizational resources, both members and other resources; Fifth, the four points above lead to the achievement of goals effectively and efficiently. This article aims to analyze the implementation of participatory management in planning, decision making, implementation and evaluation for quality improvement in Madrasahs in Tulang Bawang district, Lampung Province. This research was conducted at Madrasahs in Tulang Bawang district, Lampung. This study uses a qualitative method. Data collection techniques using in-depth interviews, observation and documentation. Research sources included the head of the Ministry of Religious Affairs in Tulang Bawang district, a sample of madrasah heads, deputy head of madrasah, and students. Data analysis was carried out interactively and continued continuously to completion.The results showed that 1) planning, namely an assessment of the madrasah environment, needs to be carried out at the beginning. The environmental assessment is divided into two, the first is an analysis of the internal environment, this means an analysis that occurs within the madrasa environment. Second, external environmental assessment means parties outside the madrasah.Then the determination of the strategic direction which is an activity to formulate or review the direction of organizational goals that are contained in the vision, mission and values in educational institutions. Madrasahs in Tulang Bawang Regency have made a neat and structured draft. So that at any time it can be read or studied to implement participatory management in Madrasahs in Tulang Bawang Regency. Furthermore, quality objectives are the goals or targets of a madrasah in carrying out a process that is to be achieved within a certain period of time. The targets in Madrasahs in Tulang Bawang Regency are the achievement of an ideal study group ratio with an ideal learning space, the absorption of the number of students from various components of society as educational customers. increase in the acquisition of National exam and exam scores every year. the school institution that is the choice of the community because of the achievement that is its priority. the achievement of complete facilities and infrastructure in accordance with the ratio of the number of students, madrasah in Tulang Bawang Lampung district as the madrasah that is most loved, and in demand by the community. 3) decision making, namely, decision making in the context of implementing participatory management programs in a sub-focus to mobilize funding resource planning, administrative activities, coordination and program elaboration. In driving the planning of financial resources, administrative activities, coordination and program elaboration. The program that has been carried out by Kasi Mapenda / Penmad and external parties at Madrasahs in Tulang Bawang Regency prioritizes models, because the model is a pattern of something to be made or produced. 4) evaluation, which aims to determine the progress of the organization, as well as the obstacles and challenges faced in implementing strategic management. the results of the evaluation will be used as feedback to the organization to determine the achievement of quality implementation. The program that has been carried out by Kasi Mapenda / Penmad and external parties is conducting coordination meetings with UPA and the Education Office related to the quality of graduation, conducting BOS reporting financial training activities with the Palembang Training Center, monitoring all Madrasahs related to 8 Education Standards, in collaboration with UPA Team. as well as the obstacles and challenges faced in implementing strategic management. the results of the evaluation will be used as feedback to the organization to determine the achievement of quality implementation. The program that has been carried out by Kasi Mapenda / Penmad and external parties is conducting coordination meetings with UPA and the Education Office related to the quality of graduation, conducting BOS reporting financial training activities with the Palembang Training Center, monitoring all Madrasahs related to 8 Education Standards, in collaboration with UPA Team. as well as the obstacles and challenges faced in implementing strategic management. the results of the evaluation will be used as feedback to the organization to determine the achievement of quality implementation. The program that has been carried out by Kasi Mapenda / Penmad and external parties is conducting coordination meetings with UPA and the Education Office related to the quality of graduation, conducting BOS reporting financial training activities with the Palembang Training Center, monitoring all Madrasahs related to 8 Education Standards, in collaboration with UPA Team